POLITICAL DYNAMICS OF MALAY ISLAM: A CONCEPTUAL-HISTORICAL STUDY - Arditya Prayogi; Singgih Setiawan; Jilma Dewi Ayu Ningtyas (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Historically-politically, Islam has become part of the traditional Malay states (palities). The Islamic-Malay relationship is manifested in a political conception of the legitimacy of the kingdom/sultanate, especially referring to the sultanate of Malacca. Since the time of the Malacca sultanate, the role of Islam has become something that cannot even be contested. Politically, Islam has become a unifying factor for the Malays. In short, the Islamic discourse has penetrated and embedded itself into the identity of the Malay community so that it also gave rise to the political variant of Malay Islam. The article aims to describe the political conception of Malay Islam starting from its background, political relations between Islam and Malays, to the dynamics and political concepts adopted by the Malay (Islam) community. This article was written using a qualitative approach based on a literature review using descriptive analytical techniques. This article shows that there is a close natural relationship between Islamic and Malay political identity. The journey of Malay-Islamic political relations which began during the Islamic sultanate continued to be dynamic until the colonialism and revivalism period which marked the change in Malay cultural identity through identity politics with the nation state channel. Malay which originally meant race/ethnicity was then delimited by regional boundaries which made it impossible for the emergence of a pan-Malay political identity.